2017
DOI: 10.1002/jssc.201601406
|View full text |Cite
|
Sign up to set email alerts
|

Flexible and powerful strategy for qualitative and quantitative analysis of valepotriates in Valeriana jatamansi Jones using high‐performance liquid chromatography with linear ion trap Orbitrap mass spectrometry

Abstract: Valeriana jatamansi Jones is an important medicinal plant and its quality is closely related to its region of origin. In the current study, we utilized a flexible and powerful strategy for comprehensive evaluation of the quality diversity for 15 regions in China. The method was based on a hybrid linear ion trap-Orbitrap mass spectrometry platform. For structure characterization, fragmentation patterns were detected by analyzing a series of standard compounds using data dependent multistage mass spectrometry ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Accurate mass measurements of the positive precursor and product ions masses were simultaneously performed, as shown in Figure S2. Seventeen putative metabolites belonging to iridoids of the CPT pathway were simultaneously annotated and identified based on their retention times, MS and MS/MS data compared with standards, if available, and with those previously published common standards, as shown in Table 2 and Figure S1A1–4 [28,29]. According to the backbone structure of compounds, among the 17 compounds identified, as shown in Figure S1B, 1 tryptamine, 2 iridoids or secoiridoids (loganic acid, secologanic acid), 2 compounds belonging to MIA strictosidinic acid, 3 compounds belonging to the vincosamide group (strictosamide, strictosamide epoxide, strictosamide diol), 8 compounds belonging to the pumiloside group (strictosamide ketolactam, pumiloside, deoxypumiloside), and 1 MIA camptothecin were included [12].…”
Section: Resultsmentioning
confidence: 99%
“…Accurate mass measurements of the positive precursor and product ions masses were simultaneously performed, as shown in Figure S2. Seventeen putative metabolites belonging to iridoids of the CPT pathway were simultaneously annotated and identified based on their retention times, MS and MS/MS data compared with standards, if available, and with those previously published common standards, as shown in Table 2 and Figure S1A1–4 [28,29]. According to the backbone structure of compounds, among the 17 compounds identified, as shown in Figure S1B, 1 tryptamine, 2 iridoids or secoiridoids (loganic acid, secologanic acid), 2 compounds belonging to MIA strictosidinic acid, 3 compounds belonging to the vincosamide group (strictosamide, strictosamide epoxide, strictosamide diol), 8 compounds belonging to the pumiloside group (strictosamide ketolactam, pumiloside, deoxypumiloside), and 1 MIA camptothecin were included [12].…”
Section: Resultsmentioning
confidence: 99%
“…To investigate, we screened the natural product library composed of ~1400 compounds. The cell viability assay showed that AVT, one of the most active valpotriate components derived from the herbal plant Valeriana jatamansi Jones [21], displayed potent GBM cell death-inducing activity in both cell lines (Fig. 6a).…”
Section: The Natural Product Avt Induces Gbm Cell Apoptosismentioning
confidence: 99%
“…HPLC standards were prepared at a concentration of 20 mg/L in methanol HPLC grade. Dilutions were prepared in a range of 0.05 to 1 mg/L in ethanol/water 70/30% (v/v) [52,53].…”
Section: Uhplc-ms/ms Analysismentioning
confidence: 99%